Effects of increasing stocking density on finishing pig performance - Potter, M. L.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 1,201 finishing pigs (initially 63 lb) were used in a 99-d growth trial to evaluate the effects of increasing stocking density on finishing pig growth performance. Single-sex pens of barrows and gilts were blocked to minimize variation due to gender and barn location. There were 12 pens per block with 3 replication pens per treatment within each block. Pens of pigs were randomly allotted to 1 of 4 treatments with 12 pens per treatment. Treatments were stocking pens with 22, 24, 26, or 28 pigs each, allowing 8.2, 7.5, 6.9, and 6.4 ft2 per pig, respectively. Pens of pigs were weighed and feed intake was determined on d 0, 14, 28, 42, 56, 70, 84, and 99 to calculate ADG, ADFI, and F/G. Pigs were fed common diets throughout the trial. No adjustments were made at the pen level to account for space increases because of removed pigs. Overall, as stocking density increased, ADG and ADFI decreased (linear; P < 0.001), but there were no differences (linear; P = 0.99) in F/G. These performance differences resulted in off-test (d 99) pig weights decreasing (linear, P < 0.001) as stocking density increased. These data indicate that in this commercial barn, finisher pig ADG and ADFI improved as the number of pigs in each pen was reduced. However, based on an economic model, income over feed and facility cost per pig placed was numerically optimized when pens were stocked with 24 pigs each, allowing 7.5 ft2 of floor space per pig.
Keywords: Swine; Growth; Space allowance; Stocking density